KAWIA : RITUAL PERKAWINAN PADA ORANG CIA-CIA WABULA DI DESA WABULA KECAMATAN WABULA KABUPATEN BUTON - Novianti Novianti; La Janu (KABANTI : Jurnal Kerabat Antropologi, 2023)
The marriage rituals of the cia-cia wabula people in wabula Village show that in the marriage customs of the Wabula people recognize 2 (two) forms of marriage, namely marriage ramai (kawia rame) and marriage lari (kawia popolaiaso). marriage ramai (kawia rame) is a marriage that occurs in accordance with the expectations of parents whose sequence follows the sequence of procedures and protocols that have been determined by official custom and are openly known to the public. The stages of implementation include the pisoloi stage (tracing the candidate), the kabheka-bheka stage (peeking, reviewing the prospective wife), the tauano pulu stage (binding words), losa (proposal and proposal), the bhawa ano tangabha stage (delivering the proposal), langgoa (the process of setting foot for the first time at the prospective wife's house), bhawa'ano singkaru (delivering the fiancÃ©'s ring), and the kawia stage (marriage ceremony) While a runaway marriage (kawia popolaiaso) is a marriage which in its implementation does not follow the rules of the applicable marriage customs. While kawi popolaiaso is carried out in stages: (a) the lovers are of the same mind to elope secretly; (b) the two of them arrive at the residence of the local priest or KUA. Â